Estimation of fading parameter correlation for modeling the land mobile satellite channel - Heuberger, Albert; et al. (Proceedings, 7th IEEE International Symposium on Broadband Multimedia Systems and Broadcasting (BMSB 2012), 2012)
This paper addresses the correlation of fading signal parameters for dual-satellite land mobile satellite (LMS) channels. We use Loo's model to describe the slow and fast variations that occur due to varying shadowing conditions and multipath fading, respectively. Loo's parameters (mean power of direct signal component, standard deviaton of direct signal component, and average multipath power) are estimated segment-by-segment from fading signals of two simultaneously measured geostationary satellites using a curve-fitting approach. The parameter correlation between the signals of the two satellites is investigated. A significant correlation is found in the mean power of the direct signal components in some environments, when both satellites are shadowed or blocked by obstacles. © 2012 IEE
UnivIS-Import:2015-04-16:Pub.2012.tech.IE.komele.estima
Keywords: channel modeling; land mobile satellite channel; Loo parameter estimation; propagation